Increase of theta/gamma ratio is associated with memory impairment - Moretti, D.V.; Fracassi, C.; Pievani, M.; Geroldi, C.; Binetti, G.; Zanetti, O.; Sosta, K.; Rossini, P.M.; Frisoni, G.B. (Clinical neurophysiology, 2009)
In this study the theta/gamma ratio was investigated as early marker of cognitive decline. Forty-nine subjects with mild cognitive impairment (MCI) underwent EEG recording and MRI scan. The theta/gamma ratio of the relative power at the peak frequency was computed. Based on the tertiles values of the ratio, three groups with increasing values of theta/gamma ratio were obtained. The groups were characterized by the performance on cognitive tests. Changes in functional brain connectivity, as expressed by interhemisperic and intrahemispheric EEG linear coherence in the groups were also evaluated. Increase in theta/gamma ratio was associated with impairment in memory tests. This relationship was confirmed by correlation and multiple regression analysis. An independent association was found between theta/gamma ratio and alpha3/alpha2 power ratio. Coherence analysis showed modifications of interhemispheric functional coupling on temporal regions on slow frequencies. Theta/gamma ratio of relative power at peak frequency is significantly associated to memory decline. It could be a useful tool in detecting MCI subjects which are at major risk to develop Alzheimer’s disease (AD) or other dementias. A global modulation of brain rhythms could be driven by the pathological alterations of theta/gamma ratio.